Echo – On One Marginal Motif in Old Croatian Literature - Šundalić, Zlata; MATELJAK POPIĆ, Anela (Anafora, 2023)
The paper explores the occurrence, meaning, and function of the echo motif in Old Croatian Literature through five focal points. The first part presents the echo motif, which was often named differently by Croatian authors. It analyzes the story of Narcissus and Echo from Ovid’s Metamorphoses, juxtaposes it to the modes of the imaginary (echo, shadow, mirror) and the mirror structure, and defines the corpus of primary texts – eighteen works from the sixteenth, seventeenth, and eighteenth centuries. The second part explores the echo motif in the works of M. Vetranović Čavčić, N. Nalješković, S. Bobaljević Mišetić, F. Lukarević Burina, and M. Gazarović. The third part reveals the relationship between the seventeenth-cenutry Croatian authors and the echo motif, analyzing the works of I. Gundulić, Dž. Bunić Vučić, J. Palmotić, V. Skvadrović, P. Zrinski, P. Ritter Vitezović, F. Krsto Frankopan, and J. Habdelić. The fourth part examines the work of eighteenth-century Croatian authors, A. Gleđević, J. Kavanjin, A. Kanižlić, M.P. Katančić, V. Došen, and the comedy Gospodarica od Elide [The Mistress of d’Elide] by an anonymous author. The paper argues that the echo motif occurs frequently in a more serious context, and less frequently in a comedic context, and that it is connected with romantic, reflexive, tragic, and quotidian topics. In addition, the echo motif offers an auditive expansion of space and, in terms of a mirror structure, functions as an imaginary double that contributes to a specific character’s awareness of self and the world around them.